Comparative genomic analysis of obligately piezophilic Moritella yayanosii DB21MT-5 reveals bacterial adaptation to the Challenger Deep, Mariana Trench. Issue 7 (28th July 2021) - Zhang, Wei-Jia; Zhang, Chan; Zhou, Siyu; Li, Xue-Gong; Mangenot, Sophie; Fouteau, Stéphanie; Guerin, Thomas; Qi, Xiao-Qing; Yang, Jian; Bartlett, Douglas H.; Wu, Long-Fei
Abstract : Hadal trenches are the deepest but underexplored ecosystems on the Earth. Inhabiting the trench bottom is a group of micro-organisms termed obligate piezophiles that grow exclusively under high hydrostatic pressures (HHP). To reveal the genetic and physiological characteristics of their peculiar lifestyles and microbial adaptation to extreme high pressures, we sequenced the complete genome of the obligately piezophilic bacterium Moritella yayanosii DB21MT-5 isolated from the deepest oceanic sediment at the Challenger Deep, Mariana Trench. Through comparative analysis against pressure sensitive and deep-sea piezophilic Moritella strains, we identified over a hundred genes that present exclusively in hadal strain DB21MT-5. The hadal strain encodes fewer signal transduction proteins and secreted polysaccharases, but has more abundant metal ion transporters and the potential to utilize plant-derived saccharides. Instead of producing osmolyte betaine from choline as other Moritella strains, strain DB21MT-5 ferments on choline within a dedicated bacterial microcompartment organelle. Furthermore, the defence systems possessed by DB21MT-5 are distinct from other Moritella strains but resemble those in obligate piezophiles obtained from the same geographical setting. Collectively, the intensive comparative genomic analysis of an obligately piezophilic strain Moritella yayanosii DB21MT-5 demonstrates a depth-dependent distribution of energy metabolic pathways, compartmentalization of important metabolism and use of distinct defence systems, which likely contribute to microbial adaptation to the bottom of hadal trench.